The routine pre-employment screening chest radiograph: Should it be routine? - Samuel V, John; Gibikote, Sridhar; Kirupakaran, Henry (Indian Journal of Radiology and Imaging, 2016)
Background and Objective: A routine chest radiograph is mandatory in many institutions as a part of pre-employment screening. The usefulness of this has been studied over the years keeping in mind the added time, cost, and radiation concerns. Studies conducted outside India have shown different results, some for and some against it. To our knowledge, there is no published data from India on this issue. Materials and Methods: A retrospective review of the reports of 4113 pre-employment chest radiographs done between 2007 and 2009 was conducted. Results: Out of 4113 radiographs, 24 (0.58%) candidates required further evaluation based on findings from the screening chest radiograph. Out of these, 7 (0.17%) candidates required appropriate further treatment. Interpretation and Conclusions: The percentage of significant abnormalities detected which needed further medical intervention was small (0.17%). Although the individual radiation exposure is very small, the large numbers done nation-wide would significantly add to the community radiation, with added significant cost and time implications. We believe that pre-employment chest radiographs should be restricted to candidates in whom there is relevant history and/or clinical findings suggestive of cardiopulmonary disease.
Keywords: Chest radiograph; pre-employment; routine; screening; usefulness